Meningkatkan Partisipasi Aktif Siswa Kelas IV melalui Penerapan Model Problem Based Learning dan Strategi Pembelajaran Terdiferensiasi - Imamatut Tarbiyah; Hendratno Hendratno; Eka Mardiana (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  This  classroom  action  study  was  designed  to  increase  the learning engagement of class IV students at SDN Wiyung 1/453 Surabaya, which previously seemed less than optimal. The intervention implemented is a Problem Based Learning (PBL) model combined with a differentiation approach. The research took place in two rounds, with each round including three phases: preparation, implementation, and evaluation. Data collection was carried out through observations of 30 students by two independent observers. Analysis involves comparing the results of observations before the intervention, during the  first round, and during the second round. The findings showed a significant increase in student learning engagement, namely from 51.36% before the intervention, increasing to an average of 58.75% in the first round, and reaching an average of 77.5% in the second round. These results indicate that the combination of PBL and differentiation strategies is successful in encouraging students' active participation in the learning process. This study provides an important contribution as a reference for teachers in efforts to increase student engagement in the classroom, especially at the elementary school level.Abstrak: Penelitian tindakan kelas ini dilakukan untuk meningkatkan keaktifan belajar siswa kelas IV SDN Wiyung 1/453 Surabaya, yang berdasarkan observasi prasiklus masih tergolong rendah. Intervensi yang diterapkan adalah model Problem Based Learning (PBL) yang dipadukan dengan pendekatan diferensiasi.. Penelitian dilaksanakan dalam dua siklus, di mana setiap siklus terdiri dari tiga tahap: perencanaan, pelaksanaan, dan refleksi. Data diperoleh melalui observasi terhadap 30 siswa oleh dua pengamat independen. Analisis melibatkan perbandingan hasil observasi sebelum intervensi, selama putaran pertama, dan selama putaran kedua. Temuan menunjukkan peningkatan signifikan dalam keterlibatan belajar siswa, yaitu dari 51,36% sebelum intervensi, meningkat menjadi rata-rata 58,75% pada putaran pertama, dan mencapai rata-rata 77,5% pada putaran kedua. Temuan ini mengindikasikan bahwa model PBL dengan strategi berdiferensiasi berhasil mendorong partisipasi aktif siswa dalam pembelajaran. Studi ini memberikan kontribusi penting sebagai referensi bagi pendidik dalam upaya meningkatkan keaktifan siswa di kelas, terutama di tingkat sekolah dasar.